Kajian Karya-Karya I Nyoman Erawan, antara Tradisi dan Modernitas - I Wayan Seriyoga Parta; Yustiono Yustiono; Nuning Y. Damayanti (ITB Journal Publisher, LPPM ITB, 2013)
I Nyoman Erawan is an artist who develops abstraction shape manner by fusing formal aspects (line, area, color and texture), with the symbols in the Balinese culture tradition which is absorbed by his own religious experience as a part of Hinduism Balinese Community. The experience exists and gives deep influence to his works, when he took art study at Indonesian Art Institute of Yogyakarta in the year of 1980 and then was introduced to modern art included to its' technique and concept. The Nyoman Erawan's works development in presenting the values of the tradition and modernity can be seen from three aspects, which includes; technique, medium and theme. The exploration of Nyoman Erawan's technique and medium was begun from two dimension artworks in1982, painting technique and assemblage, collage various materials was fused for his works and then it developed become installation work in 1993-1994, and has become performance work since 1996. The tradition values in his work are presented in west modern art manner. He uses the modernity spirit to preserve the tradition value. He represents the development of modernity in different way than modernity in West context. This is a development of his work.